2002
DOI: 10.1101/gad.982902
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces Rrm3p, a 5′ to 3′ DNA helicase that promotes replication fork progression through telomeric and subtelomeric DNA

Abstract: In wild-type Saccharomyces cerevisiae, replication forks slowed during their passage through telomeric C1–3A/TG1–3 tracts. This slowing was greatly exacerbated in the absence of RRM3, shown here to encode a 5′ to 3′ DNA helicase. Rrm3p-dependent fork progression was seen at a modified Chromosome VII-L telomere, at the natural X-bearing Chromosome III-L telomere, and at Y‘-bearing telomeres. Loss of Rrm3p also resulted in replication fork pausing at specific sites in subtelomeric DNA, such as at inactive replic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
346
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(359 citation statements)
references
References 49 publications
13
346
0
Order By: Relevance
“…3). This characteristic DNA replication profile has been demonstrated previously for rrm3 mutants, and is proposed to be a consequence of increased origin usage, coupled with genome-wide RF stalling at 41,000 predicted sites in rrm3 mutants 10,[27][28][29] . We also observed that two tandem arrays of 3xTer modules (when the origin-distal array was arranged in either the permissive or restrictive orientation) behaved similarly in both wild-type and rrm3 strains ( Supplementary Fig.…”
Section: Tus-ter Modules Cause Polar Rf Pausing In Yeast the 21-bpmentioning
confidence: 79%
“…3). This characteristic DNA replication profile has been demonstrated previously for rrm3 mutants, and is proposed to be a consequence of increased origin usage, coupled with genome-wide RF stalling at 41,000 predicted sites in rrm3 mutants 10,[27][28][29] . We also observed that two tandem arrays of 3xTer modules (when the origin-distal array was arranged in either the permissive or restrictive orientation) behaved similarly in both wild-type and rrm3 strains ( Supplementary Fig.…”
Section: Tus-ter Modules Cause Polar Rf Pausing In Yeast the 21-bpmentioning
confidence: 79%
“…Since deletion of ScPIF1 leads to an increase in mitochondrial DNA point mutations, particularly after oxidative damage (21,51,52,67), it is also possible mPif1 plays a nonessential role in mitochondrial genome stability. Although Scrrm3⌬ cells do not exhibit changes in GCR or mitochondrial genome stability, these cells do exhibit genetic instability, presumably due to replication fork pausing at specific chromosomal loci, such as the ribosomal DNA locus (31,32,45,59,68,69). ScRRM3 and ScPIF1 exhibit genetic interactions (including synthetic lethality) with many gene products required in DNA replication and S-phase checkpoint arrest (1,2,17,50,58,59,69,71).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike Rrm3 and Pif1, Pfh1 is essential (77). Rrm3 promotes the progression of replication forks at particular chromosomal loci prone to pausing during DNA replication (including the telomere), and rrm3⌬ cells exhibit a modest telomere lengthening (11,32,33,45,59,69). Mutation of ScPif1 leads to telomerase-dependent telomere lengthening (33,76), and this phenotype depends on the ATPunwinding activity of ScPif1; the enzyme has a preference for short (Ͻ30 nucleotides) RNA-DNA hybrids and can unwind telomerase RNA from a telomeric DNA substrate (15).…”
mentioning
confidence: 99%
“…Only in recent years did it become apparent that even the semiconservative replication of telomeric DNA is difficult, requiring specialized helicases and telomerebinding proteins. In S. cerevisiae, the Rrm3 5 0 -3 0 helicase prevents replication fork stalling at telomeres (Ivessa et al 2002;Makovets et al 2004). In fission yeast, it was noted that efficient replication of telomeric DNA requires the telomere-binding protein Taz1 (Miller et al 2006).…”
Section: Telomerasementioning
confidence: 99%